(3TQM GdNdGUI aj GdMSGH dHgGA GdOjf GdYGedjs - (3GdeGFj GdLdj, GHf GdeGA, YeQ Hf CMeOs
(3ChdgG (B:s
(3HSe Gddg bhdg fMeOc Cbhd CQOa GdJSejI HGdJMejO COGA dMb HYV fYeGFg GdLejd hfHP ef BdGFg GdLRjd GdJj ef LedJgG GdJhajb HeKd gPG GdJUfja hGdJObjb ddeYGfj GdehVhYI aj gPG GdJCdja s
(3BNQgG (B:s
(3bhdg hHYO ESbGW GdeTJQc hgh GdNeSI hGdYTQhf hGdeGd ef GdWQajf jHbi aj GdWQa GdChd YTQI CTjGA eYGOdI dNeSI hSHYjf aj GdWQa GdBNQ hgh GdeSCdI GdChdi Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdQjGVjGJs